PEMBERDAYAAN MASYARAKAT MELALUI PENGOLAHAN IKAN MENJADI ABON DAN NUGGET IKAN - Sitti Khotijah (ABDINA: Jurnal Sosial dan Pengabdian kepada Masyarakat, 2023)
The Potency of natural resources, in this case fishes, is one of the important asset and have goodprospect in empowering the society. So that, fishes as natural resources were required to get special attention both in managing and processing so the high protein in fishes could be safe. The fishes that naturally soon be rotten, need to processed by the innovation and creativity of the society thus the fishes will still have the worth selling. The empowerment program that conducted by all member of P@M Institute Dirosat Islamiyah Al-Amien at Tamberuh Timur village empowered the society by increasing the fishes as their natural resources potency inti Abon Wolez and Nugget Wolez Wolez. The mothed used in this program is ABCD methods, and the result of this program is processed fishes into Abon Wolez and Nugget Wolez were conducted in many steps as follows: First, Preparation. Field survey, observation, and interview with the villager of Tamberuh Timur.Second, Choosing the superior assets as priority. Third, Action-socialization. Fourth, Implementation. Are product training and product launching. Fifth, Sharing product and closing the P2M program. The inhibitingfactors found are: thr lack of social organization of community, the lack of facilities and infrastuctures.Akbar, Idham Nourgama, and Dwi Sulistiani. “Peran Organisasi Sosial Preman Super Dalam Pemberdayaan Perempuan Di Malang Raya.” Jurnal Kesetaraan dan Keadilan Gender 14, no. 1 (2019).Dumasari. Dinamika Pengembangan Masyarakat Partisipatif. Yogyakarta: Universitas Muhammadiyah Purwokerto Press Bekerjasama dengan Pustaka Pelajar Yogyakarta, 2014.Gemaputri, Ariesia A. “Tingkat Pemanfaatan Sumber Daya Ikan Hasil Tangkapan Di Perairan Jember.” Jurnal Perikanan (J.Fish, Sci) XV, no. 1 (2013): 35–41.Gendalasari, Gen Gen. “Pembinaan Organisasi Sosial Kemasyarakatan Mengenai Dampak Pandemi Covid-19 Terhadap Budaya Organisasi Di Kecamatan Tamansai Kabupaten Bogor.” JADKES, jurnal Abdimas Dedikasi Kesatuan 1, no. 1 (2020): 21–23.Hamid, Hendrawati. Manajemen Pemberdayaan Masyarakat. Makasar: De La Macca, n.d.Juwita, Tita Meirina, and Dadang Hermawan. “Implementai Kebijakan Organisasi Kemasyarakatan Di Kabupaten Bandung.” JIMIA: Jurnal Iliah Magister Ilmu Administrasi 12, no. 2 (2018).Maulana, Mirza. “Asset-Bassed Community Development: Strategi Pengembangan Masyarakat Di Desa Wisata Ledok Sambi Kaliurang.” Empower : Jurnal Pengembangan Masyarakat Islam 4, no. 2 (2019).Purbantara, Arif, and Mujianto. KKN Desa Tematik Desa Membangun Pemberdayaaan Masyarakat Desa”. Kementrian Desa, Pembangunan Daerah Tertinggal dan Transmigrasi Republik Indonesia, n.d.Riyanti, Chika, and Santoso Tri Raharjo. “Asset Based Community Development Dalam Program Corporate Social Responsibility (CSR).” Jurnal Kolaborasi Resolusi Konflik 3 (2021): 115–126.Zakky, Nurdody, Isdiantoni, and Isnani Yuli Andini. “Analisis Potensi Dan Tingkat Perkembangan Desa Di Kabupaten Sumenep.” Jurnal performance Bisnis dan Akuntansi VII, no. 1 (2017): 67.